2021
DOI: 10.3390/admsci11040106
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the Big-5 Model and Effectuation versus Causation Logics of Entrepreneurs in New Ventures: The Estonian IT Sector

Abstract: This study aims to investigate the influence of the big-5 personality traits on causation and effectuation decision-making logics using the entrepreneurial process theory. This is an empirical study based on 113 surveys of managers/entrepreneurs from the Estonian IT sector. The questionnaire was uploaded onto the online platform of connect.ee and the participants were invited to complete it. The study reveals that only conscientiousness positively and significantly predicts causation logic. However, four of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 93 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…Prior studies find that an entrepreneur who is dominant in agreeableness personality trait has a vision for business success ( Teruel-Sánchez et al, 2021 ) and the allure of the business longevity ( Honjo and Kato, 2022 ). Additionally, it has been demonstrated that the agreeableness personality trait positively correlates with business success because such an entrepreneur places importance in establishing internal networking values and culture ( Coudounaris and Arvidsson, 2021 ). We, therefore, expect a positive relationship between the descendant entrepreneur’s agreeableness personality trait and the small family business’s succession success.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Prior studies find that an entrepreneur who is dominant in agreeableness personality trait has a vision for business success ( Teruel-Sánchez et al, 2021 ) and the allure of the business longevity ( Honjo and Kato, 2022 ). Additionally, it has been demonstrated that the agreeableness personality trait positively correlates with business success because such an entrepreneur places importance in establishing internal networking values and culture ( Coudounaris and Arvidsson, 2021 ). We, therefore, expect a positive relationship between the descendant entrepreneur’s agreeableness personality trait and the small family business’s succession success.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…In their paper, Chandler et al. (2011) used 13 items and Coudounaris and Arvidsson (2021) used 12 items to measure the key dimensions of effectuation. The scale was measured using five-point Likert scale, anchored by “not at all” and “very much.”…”
Section: Methodsmentioning
confidence: 99%
“…Factors influencing knowledge management are agreeableness and knowledge self-efficacy (Baker et al, 2021;Coudounaris & Arvidsson, 2021;Lynn, 2021;Asiaei & Jusoh, 2015). Trust is an individual factor and is the main requirement in knowledge management (Asiaei & Jusoh, 2015).…”
Section: Introductionmentioning
confidence: 99%